2008
DOI: 10.1029/2007jb005307
|View full text |Cite
|
Sign up to set email alerts
|

A new active tectonic model for the construction of the Northern Apennines mountain front near Bologna (Italy)

Abstract: [1] We integrate existing and new geologic data [REtreating TRench, Extension, and Accretion Tectonics (RETREAT project)], particularly on the origin, growth, and activity of the mountain front at Bologna, Italy, into a new model that explains Apennine orogenesis in the context of a slab rollback -upper plate retreat process. The Bologna mountain front is an actively growing structure driving rock uplift $1 mm/year, cored by a midcrustal flat-ramp structure that accommodates ongoing shortening driven by Adria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
185
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(197 citation statements)
references
References 93 publications
11
185
1
Order By: Relevance
“…1b) and a complex deformation pattern resulting from an active stress field characterised by predominant extension in the Tyrrhenian (internal) side and compression in the Adriatic (external) sector of the chain (e.g., Mariucci et al 1999). Consequently, normal faulting is the dominant active deformation style in the Tyrrhenian area, whereas the active tectonics of the Adriatic sector is accommodated by folding and thrusting (Benedetti et al 2000(Benedetti et al , 2003Burrato et al 2003;Vannoli et al 2004;Boccaletti et al 2004;Basili and Barba 2007;DISS Working Group 2007;Picotti and Pazzaglia 2008;Wilson et al 2009). Active shortening is well constrained by the analysis of earthquake fault plane solutions (e.g., Gasparini et al 1985;Boccaletti et al 1985;Anderson and Jackson 1987;Frepoli and Amato 1997;Selvaggi et al 2001;Pondrelli et al , 2004Lavecchia et al 2004;Chiarabba et al 2005;Piccinini et al 2006;Boncio and Bracone 2009), stress analysis (e.g., Mariucci et al 1999;Mariucci and Muller 2003;Montone et al 2004), and geodetic measurements (e.g., Battaglia et al 2004;Serpelloni et al 2005;D'Anastasio et al 2006).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1b) and a complex deformation pattern resulting from an active stress field characterised by predominant extension in the Tyrrhenian (internal) side and compression in the Adriatic (external) sector of the chain (e.g., Mariucci et al 1999). Consequently, normal faulting is the dominant active deformation style in the Tyrrhenian area, whereas the active tectonics of the Adriatic sector is accommodated by folding and thrusting (Benedetti et al 2000(Benedetti et al , 2003Burrato et al 2003;Vannoli et al 2004;Boccaletti et al 2004;Basili and Barba 2007;DISS Working Group 2007;Picotti and Pazzaglia 2008;Wilson et al 2009). Active shortening is well constrained by the analysis of earthquake fault plane solutions (e.g., Gasparini et al 1985;Boccaletti et al 1985;Anderson and Jackson 1987;Frepoli and Amato 1997;Selvaggi et al 2001;Pondrelli et al , 2004Lavecchia et al 2004;Chiarabba et al 2005;Piccinini et al 2006;Boncio and Bracone 2009), stress analysis (e.g., Mariucci et al 1999;Mariucci and Muller 2003;Montone et al 2004), and geodetic measurements (e.g., Battaglia et al 2004;Serpelloni et al 2005;D'Anastasio et al 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Active shortening is well constrained by the analysis of earthquake fault plane solutions (e.g., Gasparini et al 1985;Boccaletti et al 1985;Anderson and Jackson 1987;Frepoli and Amato 1997;Selvaggi et al 2001;Pondrelli et al , 2004Lavecchia et al 2004;Chiarabba et al 2005;Piccinini et al 2006;Boncio and Bracone 2009), stress analysis (e.g., Mariucci et al 1999;Mariucci and Muller 2003;Montone et al 2004), and geodetic measurements (e.g., Battaglia et al 2004;Serpelloni et al 2005;D'Anastasio et al 2006). However, the knowledge of the main recent and active structures remains limited to scattered areas (e.g., Benedetti et al 2003;Burrato et al 2003;Vannoli et al 2004;Piccinini et al 2006;Picotti and Pazzaglia 2008;Picotti et al 2009;Wilson et al 2009). In this paper, we aim to fill this gap by presenting a comprehensive study of the active tectonics of the external part of the Northern Apennines.…”
Section: Introductionmentioning
confidence: 98%
“…Carminati et al [14] indicated the downflexure of the Adria plate as one cause of movement, at a maximum rate of 2.5 mm/year. The possible effects of tectonic activity along the northern Apennine thrust front buried under quaternary sediments was thoroughly discussed in [20]. More sophisticated measurements now show that the recent deformation pattern of the Apennine belt and Po Plain is due to the northward movement of the Adria plate [21].…”
Section: State-of-the-art Of Subsidence In Northern Italy and Po Deltamentioning
confidence: 99%
“…With reference to the Po Plain, all of the northern Apennines belt is actively being uplifted at rates ranging from 0.1 to 2 mm/year (Spagnolo and Pazzaglia, 2005). The northern Apennines mountain front and its adjacent foothills are riddled with geomorphic and geologic evidence of recent tectonics such as active folds and faults (Picotti and Pazzaglia, 2008). However, information on the recent and active structures remains limited to scattered areas (Piccinini et al, 2006;Picotti and Pazzaglia, 2008;Picotti et al, 2009;Wilson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The northern Apennines mountain front and its adjacent foothills are riddled with geomorphic and geologic evidence of recent tectonics such as active folds and faults (Picotti and Pazzaglia, 2008). However, information on the recent and active structures remains limited to scattered areas (Piccinini et al, 2006;Picotti and Pazzaglia, 2008;Picotti et al, 2009;Wilson et al, 2009). The study area is characterized by complex structures showing the presence of different fault systems of tectonic origin Panini et al, 2002aPanini et al, , 2002bPlesi et al, 2002aPlesi et al, , 2002bSeveri et al, 2002aSeveri et al, , 2002bBalocchi, 2003;Boccaletti et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%